Analisis Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah pada Bank Sampah Lansek Manih Nagari Muaro Kabupaten Sijunjung - Ramadhana, Azhara Rizaltul; Sumarni, Nini (ARZUSIN, 2026)
The preparation of financial statements based on the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) has received attention in several studies, yet research that specifically discusses its application to community-based waste banks, particularly the Lansek Manih Waste Bank, remains limited. This study aims to analyze the preparation of financial statements based on SAK EMKM at the Lansek Manih Waste Bank in Nagari Muaro, Sijunjung Regency. This study used a qualitative approach with a case study design, involving 12 participants consisting of waste bank managers and customers selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña through the stages of data reduction, data display, and conclusion drawing. The results show that the preparation of financial statements at the Lansek Manih Waste Bank is still carried out simply through the recording of cash inflows and cash outflows, without preparing a statement of financial position, income statement, and notes to the financial statements as regulated in SAK EMKM. This study also found inconsistencies in the recording of customer savings due to a manual recording system that has not yet been structured. The low level of managers’ understanding of accounting standards and the absence of training are the main factors preventing the implementation of SAK EMKM. This finding contributes to the development of signaling theory in the context of financial management transparency in community-based organizations and broadens understanding of the implementation of SAK EMKM in waste banks. The conclusion of this study emphasizes the importance of preparing financial statements that are systematic, accountable, and compliant with standards. The practical implications of this study indicate the need for assistance and training for waste bank managers to improve the quality of financial administration and the transparency of organizational management.